Sketch map of the Buchanan Bay, Bache Peninsula, Princess Marie Bay Region of Grinnell Land / by R.E. Peary - Peary, Robert E. (Robert Edwin), 1856-1920 (1899)
Negative blueprint Relief shown by hachures "This map reproduced in the Bulletin of the American Geographical Society, vol. 31, 1899, at p. 381 illustrating note on "Peary's Sledge Journeys" -- note pasted on Color not given